2015
DOI: 10.1021/acs.jpcc.5b02532
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction of PdOx- and RuOy-Modified Tin Dioxide with CO and NH3 Gases: Kelvin Probe and DRIFT Studies

Abstract: The processes of selective interactions of gas sensitive nanocrystalline tin dioxide modified by catalytic PdO x and RuO y clusters with ppm-range concentrations of CO and NH 3 in air was studied.From simultaneous in situ work function and resistance measurements it was deduced that the modifiers promote specific interaction of gas molecules with the materials surface. In situ DRIFT studies revealed a key role of catalytic clusters in the selective gas-solid interactions. Specific CO chemisorption on Pd-sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In H 2 sensing, in the presence of O 2 , water formation occurs as expected, while at anaerobic conditions, hydrogen reacts with the metal oxide surface to create “rooted” hydroxyl groups and there is no detected desorbed water formation . In Pd/SnO 2 systems, CO activated on PdO x reacts with hydroxyls on SnO 2 surface with CO 2 formation . CH x reaction intermediates on Pt‐group active sites can be oxidized by OH ads on adjacent oxophilic Sn surface …”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In H 2 sensing, in the presence of O 2 , water formation occurs as expected, while at anaerobic conditions, hydrogen reacts with the metal oxide surface to create “rooted” hydroxyl groups and there is no detected desorbed water formation . In Pd/SnO 2 systems, CO activated on PdO x reacts with hydroxyls on SnO 2 surface with CO 2 formation . CH x reaction intermediates on Pt‐group active sites can be oxidized by OH ads on adjacent oxophilic Sn surface …”
Section: Introductionmentioning
confidence: 68%
“…[14] Our selective attention to Pd/SnO 2 was also fuelled by the fact that SnO 2 is used as sensors for CO and (less frequently) CH 4 or H 2 detection via catalytic oxidation mechanisms. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The humidity effect has been known in that field since 1970's [16][17][18][24][25][26][27][28][29][30][31][32] as it influences the sensor signal by electron generation: H 2 O + Sn lattice + O lattice $ (HOÀ Sn lattice ) + (O lattice H) + + e À . [19] SnO x surface has a high affinity to water that competes with CO adsorption; [27] the concentration of hydroxyl groups increases in the presence of gas-phase water and O 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) It is known that ruthenium compounds are active catalysts for the oxidation of nitrogen compounds [71][72][73][74]. This catalytic effect was also noted in the detection of nitrogen containing gases by SnO 2 based gas sensitive materials [75,76]. At the same time, the sensitivity of n-type semiconductor oxides to NO 2 significantly exceeds their sensitivity to NO [23].…”
Section: Resistive Response In Dark Conditionsmentioning
confidence: 91%
“…The maximum at about 3400 cm −1 of the absorption band ascribed to hydroxyl groups is evidence for a predominance of rooted hydroxyls associated via hydrogen bonds (OH…..OH) [ 49 ]. FTIR investigations and impedance measurements [ 50 , 51 ] showed that the room temperature CO sensitivity of SnO 2 /PdO x nanocomposites is precisely due to the participation of such surface OH-groups in the oxidation of chemisorbed carbon monoxide molecules via reaction (5): …”
Section: Resultsmentioning
confidence: 99%